Playing and learning with gamification: An in-class concurrent and distributed programming activity - Filev Maia, Rodrigo; Reis Graeml, Felipe (Frontiers in Education 2015 : launching a new vision in engineering education : proceedings : October 21-24, 2015, Camino Real Hotel & Conference Center, El Paso, Texas, 2015)
It seems that education is working fine, especially in several good and traditional Universities around the world. Nokia was also doing very well in a business world until clients' needs change. Are we academics really offering what the students and the labor market need and demand? We have offered the same product for decades, but we haven't realize that the client is different and is demanding another product. Sometimes, we may have the feeling that our students are beyond this world when they are connected in the internet. Some say that the new generation is not using technology in a properly way to study; however are academics using it better? We are not using the new generation's language to communicate with students and to transfer knowledge. Games and competitions is the "language of the new generation" and it may promote a desired long-term learning experience we academics always wished. This paper describes the use of gamification as a tool to support the lectures of concurrent and distributed subjects, for undergraduate students of computer science course. In the game students should create and optimize the production line of a specific product. In the programming class, students should create and balance the same production line to beat competitors. Students have to use concepts of distributed programming and concurrency, and create strategies to organize the threads (production line) in order to be more efficient than the other competitors. The best production lines sell more and get more benefits. This paper discusses the preliminary results obtained from a survey of learning inhibits, which were applied before and after doing the course activity. The study compares the results obtained in both surveys and indicate that with the use of gamification to support class activities the learning inhibits tend to reduce at same time that transversal competences are stimulate on students. The discussion conducted after each round of the game indicated the interest and motivation of the students with this type of class.